Self-Determination in the International Legal System Whose Claim, to What Right? - Sparks, Tom (Bloomsbury Academic, 2023)
This open access book brings conceptual clarity to the study and practice of self-determination, showing that it is, without doubt, one of the most important concepts of the international legal order. It argues that the accepted categorisation of internal and external self-determination is not helpful, and suggests a new typology. This new framework has four categories: the polity-based, secessionary, colonial, and remedial forms. Each will be distinguished by the grounds, or the legitimacy-claim, on which it is based. This not only ensures consistency, it moves the question out of the purely conceptual realm and addresses the practical concerns of those invoking self-determination. By presenting international lawyers with a typology that is both theoretically consistent and more practically useful, the author makes a significant contribution to our understanding of this keystone of international law. The open access edition of this book is available under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com. Open access was funded by Max-Planck-Institut für ausländisches öffentliches Recht und Völkerrecht.